"It didn't hurt me": patients' and providers' perspectives on unsupervised take-home doses, drug diversion, and overdose risks in the provision of medication for opioid use disorder during COVID-19 in San Juan, Puerto Rico - Roberto Abadie; Celia B. Fisher (BMC, 2024)
Abstract Background During the COVID−19 pandemic, clinics offering medication for opioid use disorder (MOUD) needed to rapidly introduce unsupervised take−home dosing, while relapsing patients and patients unable to enter treatment faced increased risks of fentanyl−related overdose deaths and other drug−related harms. Based on a qualitative study of people who inject drugs (PWID) receiving MOUD treatment and MOUD staff in Puerto Rico, this paper documents the lived experiences of patients and providers during this period and the risk perceptions and management strategies to address substance misuse and drug diversion attributable to unsupervised take−home−dose delivery. Methods In−depth qualitative interviews were conducted with patients (N = 25) and staff (N = 25) in two clinics providing MOUD in San Juan, Puerto Rico, during 2022. Patients and staff were receiving or providing treatment during the pandemic, and patients reported injection drug use during the past thirty days. Results Patients were overwhelmingly male (84%), unmarried (72%), and unemployed (52%), with almost half (44%) injecting one to three times a day. Mean time in treatment was 7 years. Staff had a mean age of 46 years with more than half of the sample (63%) female. The majority of patients believed that unsupervised take−home dosing had no significant effect on their treatment adherence or engagement. In contrast, providers expressed concerns over the potential for drug diversion and possible increased risks of patient attrition, overdose episodes, and poor treatment outcomes. Conclusion This study underscores the importance of insider perspectives on harm−reduction changes in policy implemented during a health crisis. Of note is the finding that staff disagreed among themselves regarding the potential harms of diversion and changes in drug testing protocols. These different perspectives are important to address so that future pandemic policies are successfully designed and implemented. Our study also illuminates disagreement in risk assessments between patients and providers. This suggests that preparation for emergency treatment plans requires enhanced communication with patients to match treatments to the context of lived experience.